An airline itinerary choice model that includes the option to delay the decision. (February 2017) - Freund-Feinstein, Uzi; Bekhor, Shlomo
Highlights: Design of a specially designed stated preference (SP) survey, which emulates an air travel website. The survey includes the option to delay the decision to choose an airline itinerary. The rich data set allows the estimation of discrete choice models of airline itinerary choice. Model estimation for four market segments: tourist and business travelers for medium- and long-haul flights. Estimation of the expected monetary value of delaying a flight purchase. Abstract: Choice situations with variable supply characteristics are found in many applications, including airline itinerary selection. This paper discusses the airline itinerary choice problem in dynamic supply settings. The paper develops a specially designed stated preference (SP) survey, which emulates an air travel website. The survey includes the option to delay the decision to choose an airline itinerary. The rich data set allows the estimation of discrete choice models of airline itinerary choice. The paper presents selected model estimation and application results for two market sectors (tourists and business travelers) and two flight types (medium-haul and long-haul flights). In addition to expected results for several level-of-service variables such as flight cost, cancellation fees, connection times and punctuality percentages, the model estimates the expected value of delaying a flight purchase.